Gradually decreasing daylength after smoltification induced by “winter signal“ reduced sexual maturation in male Atlantic salmon - Skjold, Vetle; Rørvik, Kjell-Arne; Sveen, Lene; Burgerhout, Erik; Mota, Vasco C.; Weihe, Rúni; Ytrestøyl, Trine; Bou, Marta; Jacobsen, Hans Jákup; Allaoui, Giovanni; Fuskevåg, Ole-Martin; Dessen, Jens-Erik (Frontiers in Aquaculture, 2024)
Introduction: Male maturation in seawater-adapted (smoltified) Atlantic salmon is unwanted yet frequently reported under intensive rearing conditions in land-based facilities with fish up to 1 kg. Although photoperiod regulates both smoltification and maturation, the optimal post-smoltification regimen to prevent maturation is unclear. Methods: In this study, mixed sex Atlantic salmon weighing 95 g were exposed to three different photoperiod regimes: continuous, gradually decreasing, and short-to-long daylength, after induction of smoltification by the “winter signal” (12 h:12 h light:dark). Fish were maintained under these conditions in triplicate for 18 weeks at 12°C in a brackish water flow-through system with a salinity of 20 ppt. This initial phase was followed by a grow-out period (1-2.5 kg) in seawater (32 ppt) at 13°C for 11 weeks, with exposure to decreasing daylength. Throughout the 29-week study, body condition, gonad development, and morphological traits were assessed. Additionally, during exposure to brackish water, serum 11-ketotestosterone (11-KT) was quantified, and the testes were examined histologically. At termination, maturation rate was determined. Results: This study exclusively identified maturation among male salmon. Under continuous light exposure, the number of fish initiating maturity steadily increased from week 8 and continued to increase in subsequent samplings. In the short-to-long day group, a subset of males showed elevated 11-KT levels at week 14, although gonadal development and morphological changes were not evident until week 18. Males exposed to decreasing daylength showed no substantial increase in 11-KT, although a few fish exhibited advanced gonad development by week 18. At the end of the trial, markedly lower percentages of maturing and fully mature males were observed among fish previously exposed to decreasing daylength. The maturation rates at study termination were 44.4% for short-to-long day, 29.4% for continuous light, and 4.3% for decreasing daylength. Discussion: These results show that photoperiod can be utilized to regulate maturation in Atlantic salmon males. Decreasing photoperiod after smoltification seems to limit early sexual maturation without compromising body size development. Thus, decreasing the photoperiod could be utilized to limit maturation in the production of post-smolt salmon or salmon in land-based facilities.